CURRENT USE OF NANOPARTICLES IN ENDODONTICS: A SYTEMATIC REVIEW - Andreea Marica; Lucian Sipos; Raluca Iurcov; Teodora Stefanescu; Gabriela Ciavoi; Alexandra-Ioana Lucan; Florina Miere (Groza) (Romanian Society of Oral Rehabilitation, 2022)
Nowadays, technology evolves very fast and we are witnesses of major changes in dentistry. Nanotechnology improved many fields of dentistry, including endodontics. In this paper, we compared different irrigants and sealers which are currently used in endodontic treatments, their advantages and disadvantages and their limitations. In the context of emerging trends of nanotechnology in all fields of dentistry, we aimed to highlight the importance of developing new irrigants and sealers improved with nanoparticles, with superior properties compared to traditional ones. As resulted from our research, the most used irrigants in endodontics (NaOCl, EDTA, CHX) possess different kinds of advantages, but none is flawless, also having some limitations. Also, every current sealer available on the market has one or more disadvantages. For this reason, nanotechnology is very welcomed in this field and different kinds of nanoparticles were proposed for their particularities in order to improve the performances of endodontic materials. We present in this work a review of the literature regarding different types of nanoparticles, their effects on endodontic microbiota and also, their particularities.